Pengaruh Kualitas Pelayanan, Promosi dan Lokasi terhadap Keputusan Menginap Melalui Kepuasan Pelanggan di Hotel Indonesia Kempinski Jakarta - Arnold, Hasiholan Mikael (BUDGETING : Journal of Business, Management and Accounting, 2024)
The aim of this research is to determine the quality of service to help attract new customers and researchers use quantitative descriptive methods. Sugiyono (Sugiyono, 2017) Data was collected using a questionnaire method and analyzed using a Likert scale, after which the data was processed using SmartPLS 3.0. The results of research conducted by the author at Hotel Indonesia Kempinski Jakarta, can be concluded that overall the factors of service quality, promotion and location mutually have a positive effect on the decision to stay overnight through customer satisfaction. Good and friendly service will make customers feel comfortable and appreciated, apart from that creative and innovative promotions can also make customers feel interested in staying, and strategic location can also be one of the reasons for customers to return to staying at the hotel. Keywords: Customer Satisfaction, Promotion, Stay Decision, Service Quality.